The Effectiveness of a Training Program Based on Using Augmented Reality Technique to Improve some Reading Skills for Pupils with Mild Intellectual Disabilities - Alobaidan, Fatemah Saad Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The aim of study was to, examine the effectiveness of a training program based on using augmented reality, technique to improve some reading skills (matching between the symbol of the letter and its name, distinguish between the similar letters in shape, reading a word consists of two or three letters) for pupils with mild intellectual disabilities, the study depended on the semi – experimental approach, the sample of the study consisted of (14) female pupils which were suffering from the simple intellectual disabilities enrolled in intellectual education programs at the 13th primary school, Al Khobar city Saudi Arabia, they were divided into two groups, one of them was the experimental group, it included seven female pupils, the other group was the control group, it included seven female pupils. To achieve the aims of the study, the researcher prepared the following tools,- the reading skills test and a training program based on using the augmented reality technology and the scientific content, the data were analyzed by using Statistical Package for Social Sciences program version 23 (SPSS). The results of the study were as the following: - There were statistically significant differences between the averages of ranking the marks of the experimental female pupils’ group, and the control group on reading skills test for the post scale for the favor of experimental group. - There were statistically significant differences between the averages of ranking, the marks of the experimental female pupils’ group regarding both the post and pre scale regarding the reading skills test for the favor of the post scale. - There were no statistically significant differences between the averages of ranking the marks of the experimental group of the female pupils for the post and consecutive scale about the reading skills test. The researcher suggested to establish courses for both teachers of special education in general and intellectual disability in using augmented reality technology in teaching people with intellectual disabilities various skills such as academic and social skills and self-care.